Caracterização físico-química e biológica de biomateriais e compósitos híbridos, desenhados a partir de escama de tilápia do nilo (Oreochromis Niloticus), com potencial aplicação na engenharia de reparação de tecidos ósseos - Sierra, José Jovanny Bermúdez (2020)
This work proposes the use of novel biomaterials, with potential biomedical applications, especially in the area of bone tissue engineering (repair or filling). In this research, several simple technique of Hydroxyapatite (HapP) and Collagen (Col) extraction, from the Nile Tilapia scale (Oreochromis Niloticus), using chemical hydrolysis (acid and basic) and saline precipitation respectively. The extracted and purified biomaterials, according to the physical-chemical properties were characterized by infrared (FT-IR), Thermogravimetry (TGA/DTG), Differential Scanning Calorimetry (DSC), Scanning Electronic Microscopy, (SEM-EDX) with Energy-Dispersive X-ray Spectroscopy, X-Ray Spectrometry (XRD), Raman Spectrometry (RS), Nuclear Magnetic Resonance (NMR) and Electrophoresis (SDS-PAGE). Posteriorly, xeno-hybrid polymer biocomposites of HapP/Col were designed, based on Central Composite Rotational Delineation (CCRD) associated to the Response Surface Methodology (RSM), with characterization of physical parameters (porosity, swelling, PVA and SEM). furthermore, two types of biocompatibility analysis have been developed: 1) “in vitro” cell viability of “OFCOL II” osteoblasts-like co-culture on HapP/Col biocomposites during periods of 1, 3 and 7 days, and 2) "in vivo" by subcutaneous insertion in Wistar rats of extracted biomaterials from scales (HapP and Col). In the latter, a sample of synthetic HapS and two types of the HapP/Col and HapS/Col composites, were designed and implanted in the connective tissue, which were then extracted in three periods (7, 15 and 30 days), At each date, tissue responses were assessed histomorphometrycally by degree of inflammation, proliferation of fibroblast and area of neovascularization in tissues stained with Hematoxylin and Eosin (H&E). The results obtained from the characterization analyses, demonstrate that there is a physical-chemical similarity with several researches related to biomaterials extracted from biological sources: HapP presented characteristics of ceramics with nanometric and porous structures of amorphous type and exhibited characteristics of type I Collagen with helicoidal structure of good thermal stability. The "in vitro" results showed that the best performing biocomposites in cellular bioactivity were in the concentration range between 60-75% HapP and 25-40% Col. whereas the "in vivo" results, due to the similarity of inflammatory response with the control group, demostrate that biomaterials (HapP and Col) and biocomposite presented an accelerated tissue recovery, being biocompatible to a greater extent compared to group of synthetic HapS (HapS/Col and HapS), thus, highlighting a need for future research to explore the link between biological ativities of biomaterials on "in vivo" bone neoformation. These types of biomaterials and/or biocomposites derived from the Nile Tilapia scale are likely to be suitable for use in Guided Bone Regeneration procedures with osteogenic function, specifically in xeno-hybrid forms of granulated bone grafts or polymeric biocomposites.